2011
DOI: 10.1093/ecam/neq036
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Interleukin‐10 in the Anti‐Inflammatory Effect of Sanyinjiao (SP6) Acupuncture in a Mouse Model of Peritonitis

Abstract: In this study, we determined the anti-inflammatory effect of manual acupuncture at the Sanyinjiao or Spleen 6 (SP6) point on carrageenan-induced peritonitis in mice and investigated mechanisms that may underlie this effect. In the first set of experiments, male Swiss mice were allocated into five groups: the control (sterile saline), dexamethasone (DEXA), invasive sham-acupuncture (non-acupoint), SP6 acupuncture and carrageenan-treated groups. Ten minutes after needle retention or 30 min after DEXA treatment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 44 publications
(42 reference statements)
6
43
0
1
Order By: Relevance
“…Reducing the activity of MPO using Ac has already been demonstrated in work recently published by Da Silva et al 23 , using an experimental model of peritonitis in mice. Lima et al 12 studied the effects of EAc in randomized skin flaps in rats and found significant reduction in MPO activity.…”
Section: Mpo Assaymentioning
confidence: 82%
“…Reducing the activity of MPO using Ac has already been demonstrated in work recently published by Da Silva et al 23 , using an experimental model of peritonitis in mice. Lima et al 12 studied the effects of EAc in randomized skin flaps in rats and found significant reduction in MPO activity.…”
Section: Mpo Assaymentioning
confidence: 82%
“…In mice, the SP6 acupoint has been used in the study of pain conditions and is located 2 mm proximal to the upper border of the medial malleolus, between the posterior border of the tibia and the anterior border of the Achilles tendon. [15][16][17] Needles inserted at the SP6 acupoint stimulate fibers of the flexor digitorum longus muscle and branches of the tibial nerve, which is related to the innervation of the plantar surface of the hindpaw. 18 For EA, electrical current was passed along the inserted needle for 10 min using a NKL EL-608 electrostimulator (NKL produtos eletronicos, Brusque, SC).…”
Section: Acupuncture Needlingmentioning
confidence: 99%
“…Carrageenan-induced peritonitis is a well-characterized experimental model of acute inflammation, largely employed to test new anti-inflammatory therapies, which allow researchers to quantify or analyze peritoneal vascular permeability and cellular migration as well as changes in other inflammatory parameters, such as cytokine production (Beekhuizen and Van Furth, 1993;Downey et al, 1995;Silva et al, 2011). Thus, in our study, it was possible to produce an acute inflammatory response in the peritoneal cavity of mice four hours after carrageenan injection.…”
Section: Discussionmentioning
confidence: 70%
“…It has been clearly established that leukocytes, among other cells, are a source of pro-inflammatory cytokines, i.e., TNF-a and IL-1b, released during the acute inflammation induced by carrageenan (Pereira et al, 2006;Silva et al, 2011). There is evidence that these pro-inflammatory cytokines help to propagate the extension of a local or systemic inflammatory process (Mizgerd et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation